2012
DOI: 10.1002/elan.201100702
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of 6‐Benzylaminopurine‐Copper(I) Complex on Pencil Graphite Electrode

Abstract: A voltammetric study of the 6‐benzylaminopurine (BAP)/Cu(I) system is performed. BAP is an adenine‐type cytokinin that elicits cell division in plants and presents antitumor activity when forming complexes with different transition metal ions as copper(I). In the frame of this research field, an analysis of linear sweep voltammetry (LSV), adsorptive stripping voltammetry (AdSV), and elimination voltammetry with linear scan (EVLS) data obtained with a pencil graphite electrode (PeGE), allows us to propose the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…PGEs were pretreated potentiostatically by maintaining the electrode in an electrolyte for more than 30 s at a selected potential higher than 1.3 V [ 9 , 53 , 55 , 56 , 60 , 70 , 99 101 , 105 , 192 , 193 ] or by scanning the potential at a given scan rate, for a certain number of cycles within a large potential range [ 2 , 57 , 58 , 61 , 69 , 103 , 106 , 188 , 194 ]. Some papers report a comparison between the two mentioned activation procedures and depending on the electrochemical performances obtained for the investigated analyte one of them was selected; for example, chronoamperometric activation of PGE was used for alkylphenols [ 50 ] and tannic acid [ 51 ] analysis and cyclic voltammetric activation of PGE for dopamine [ 21 ] and bisphenol A [ 54 ] detection.…”
Section: Discussionmentioning
confidence: 99%
“…PGEs were pretreated potentiostatically by maintaining the electrode in an electrolyte for more than 30 s at a selected potential higher than 1.3 V [ 9 , 53 , 55 , 56 , 60 , 70 , 99 101 , 105 , 192 , 193 ] or by scanning the potential at a given scan rate, for a certain number of cycles within a large potential range [ 2 , 57 , 58 , 61 , 69 , 103 , 106 , 188 , 194 ]. Some papers report a comparison between the two mentioned activation procedures and depending on the electrochemical performances obtained for the investigated analyte one of them was selected; for example, chronoamperometric activation of PGE was used for alkylphenols [ 50 ] and tannic acid [ 51 ] analysis and cyclic voltammetric activation of PGE for dopamine [ 21 ] and bisphenol A [ 54 ] detection.…”
Section: Discussionmentioning
confidence: 99%
“…PeGE was also used for voltammetric study of the 6-benzylaminopurine (BAP)/Cu(I) system. On the case of BAP, which is an adenine-type cytokinin that elicits cell division in plants and possesses antitumor activity when forming complexes with different transition metal ions as Cu(I) [ 200 ], it was shown that electrochemical analysis in connection with EVLS allows to propose the stoichiometry of the possible complexes formed and the mechanism for total electrode reactions of the BAP/Cu(I) system.…”
Section: Surface Modification Approaches To Enhance Electrochemical Amentioning
confidence: 99%
“…The coefficients 1 , 2 , and 3 can be obtained by solving the above three equations simultaneously using Matlab program [9,19] and their values are calculated as 1 = −11.657; 2 = 17.485; 3 = −5.8284. (5) Hence the elimination function for conservation of diffusion current with simultaneous elimination of kinetic and charging current can be given as E4 [7], simultaneous elimination of and , with conservation of :…”
Section: Theorymentioning
confidence: 99%
“…Elimination voltammetry with linear scan (EVLS), an electrochemical method comprising the elimination of some particular currents from the measurements of linear scan voltammetry was first proposed by Dracka and simultaneously verified by Trnkova in 1996 [7,8]. A large volume of work has been published by Trnková et al [8][9][10][11][12][13][14][15]. Most of these papers point to EVLS as an excellent tool to understand electrochemical processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation